ISLAMIC BANK BRAND REPUTATION IN INDONESIA - YENTI AFRIDA; M. ZAKY MUBARAK LUBIS (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to find the reputation value of Islamic banks in Indonesia. This research is a descriptive quantitative research using Net Brand Reputation and Social Network Analysis methods. This research was conducted on a BUS that has a mobile banking application using customer review data for 2016-2018. The results showed that Bank Muamalat had the highest reputation with a score of 0.607 followed by Islamic NTB Bank at 0.57, Bukopin Syariah Bank at 0.43, Mandiri Syariah Bank at 0.34, BCA Syariah Bank at 0.24, and BRI Syariah at 0 ,22.